Searching and Reviewing Literature - Husnunnisa; Sri Mulyani (al-Afkar, Journal For Islamic Studies, 2025)
Literature review is an important part of a research. Literature review is used as a basis for conducting research and a step to avoid duplication of research. This research uses a library research method by collecting information from various materials to be processed, concluded and presented simply. The results of the study show that literature review as a description of literature relevant to a particular topic not only provides a summary of research results but is also equipped with a critical assessment of the literature. By assessing and synthesizing various literatures from previous research, researchers will have a strong foundation regarding the urgency of their research